Warriors. A shadow in RiverClan - Jolley, Dan; Hunter, Erin (Harper Alley, 2020)
Feathertail is struggling trying to find her place in Riverclan after the defeat of Tigerstar and the former actions of her Clanmate's destroys her view of the clan she calls home. When a rogue cat named Sasha and her two kits come to the clan for help, Feathertail must come to terms with the past if she is going to be a part of Riverclan's future.